The massive binary companion star to the progenitor of supernova 1993J. - Maund, JR; Smartt, S; Kudritzki, R; Podsiadlowski, P; Gilmore, G (2004)
The massive star that underwent a collapse of its core to produce supernova (SN)1993J was subsequently identified as a non-variable red supergiant star in images of the galaxy M81 taken before explosion. It showed an excess in ultraviolet and B-band colours, suggesting either the presence of a hot, massive companion star or that it was embedded in an unresolved young stellar association. The spectra of SN1993J underwent a remarkable transformation from the signature of a hydrogen-rich type II supernova to one of a helium-rich (hydrogen-deficient) type Ib. The spectral and photometric peculiarities were best explained by models in which the 13-20 solar mass supergiant had lost almost its entire hydrogen envelope to a close binary companion, producing a 'type IIb' supernova, but the hypothetical massive companion stars for this class of supernovae have so far eluded discovery. Here we report photometric and spectroscopic observations of SN1993J ten years after the explosion. At the position of the fading supernova we detect the unambiguous signature of a massive star: the binary companion to the progenitor.